O19 Cortical activation variability is altered in individuals with chronic ankle instability during single limb postural control. (17th September 2017) - Rosen, AB; Mukherjee, M; Yentes, JM; McGrath, ML; Maerlender, AC
Abstract : Study Design: Cross-sectional. Objectives: Assess differences in cortical activity during single-limb stance (SLS) among controls, copers and chronic ankle instability (CAI) groups. Background: Repetitive sprain characterises CAI and may predispose individuals to early onset osteoarthritis. While, the causes and perpetuation of CAI is often disputed, functional weaknesses in cortical-motor functioning may contribute to perceived dysfunction. Methods and Measure: 31 individuals (10male, 21female: age=22.3±2.4 years, height=169.6±9.7 cm, mass=70.6±11.6 kg) participated in this study. Subjects were classified into CAI (n=11), coper (n=7), and control (n=13) groups. Participants performed a SLS on a force platform (100 Hz) for 60 s while wearing a 24-channel fNIRS system (ETG-4000 Optical Topography System). Oxy-haemoglobin (OxyHb) and deoxy-haemoglobin (DeoxyHb) changes over the superior parietal lobe (SPL), pre-central gyrus (PreCG), post-central gyrus (PostCG), and supplementary motor areas (SMA) were recorded. Differences in average and standard deviations of OxyHb and DeoxHb were assessed with analysis of variance, Tukey's post-hoc tests and cohen's d effect sizes for each area of the cortex among groups (p<0.05). Results: No differences in average OxyHb or DeoxyHb were present for any cortical areas (p>0.05). However, the CAI group displayed greater standard deviations of OxyHb in the SMA (0.58±0.73 mml/L) and PostCG (0.25±0.22 mml/L) compared to Controls (SMA:0.15±0.12 mml/L, p=0.028, d=0.82; PostCG:0.12±0.10 mml/L, p=0.043, d=0.76) and Copers (SMA:0.09±0.03 mml/L, p=0.044, d=0.95; PostCG: 0.12±0.10 mml/L, p=0.030, d=0.76). Conclusion: Individuals with CAI demonstrated large differences in SMA and PostCG cortical activation variability. Changes in PostCG activity show that during SLS, somatosensory perceptions may be significantly affected in those with CAI. For the SMA, which is important for postural stabilisation and coordination, the results suggest the CAI group may have greater variations in order to provide similar postural outcomes in relation to copers and controls. Consequently, for both the PostCG and SMA, variations in cortical activation provides evidence for an altered neural mechanism of postural control in CAI populations.